National culture and groups - Chen, Ya-Ru; Mannix, Elizabeth A., 1960-; Neale, Margaret Ann; Wageman, Ruth (Research on managing groups and teams, 2006)
This volume is based on the premise that in an era of rapid globalization, while there is a great deal of convergence on many aspects of group processes and interactions across national cultures, it is the understanding and appreciation of the divergence among people of different national cultural backgrounds that make all the difference. Contributors to this volume address two broad important questions: Do our theories of groups and teams functioning apply universally? And how do our theories apply, if at all, in multicultural settings? In addition, this volume highlights new exciting topics in the cross-cultural area: power, time, creativity, emotions, networks, and multi-cultural diversity. Together, the chapters attest to the fact that study of national culture is flourishing and important. It not only informs but also modifies and enriches theories and research of group processes and social behavior. The collective effort in this book should stimulate further inquiry regarding the role of national culture in the increasingly globalized human experience. This book features an international representation. It addresses a variety of group processes. It investigates group processes in a multi-cultural environment (i.e., a global company).